2006
DOI: 10.2298/vsp0608737r
|View full text |Cite
|
Sign up to set email alerts
|

High-density cervical ureaplasma urealyticum colonization in pregnant women

Abstract: Cervical colonization with U. urealyticum > or = 10(4) is more frequent in pregnant women with risk pregnancy than in pregnant women with normal term delivery. High-density cervical U. urealyticum colonization should be observed as a possible etiological factor for PROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(34 reference statements)
0
2
0
2
Order By: Relevance
“…Interestingly, there was also an association between HPV and U. urealyticum , but only in patients with a high colonization rate [18]. Further, high-density cervical U. urealyticum colonization may be a risk factor for premature rupture of membranes, chorioamnionitis and preterm delivery [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there was also an association between HPV and U. urealyticum , but only in patients with a high colonization rate [18]. Further, high-density cervical U. urealyticum colonization may be a risk factor for premature rupture of membranes, chorioamnionitis and preterm delivery [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…A previous research conducted in Belgrade reported the prevalence of Chlamydia trachomatis genital infection of 30.3% among sexually active female adolescents aged 19 years, who visited the National Institute for Mother and Child Health (9). Other studies were aimed at specific groups, such as women with premature delivery (10) or microorganisms closely related to Chlamydia trachomatis such as Ureaplasma (11). In general, the results mentioned above, as well as other similar studies, could suffer from selection bias since their methods were not based on epidemiological backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Существует также мнение, что определяющую роль в патогенезе неблагоприятного воздействия генитальных микоплазм на мать, плод и новорожденного играет не столько сам факт обнаружения данных микроорганизмов в половых путях матери, сколько степень их колонизации, т.е. чем выше концентрация гениталь-ных микоплазм, тем чаще наблюдаются преждевременное излитие околоплодных вод, преждевременные роды, рождение детей с низкой массой тела, послеродовый эндометрит, увеличивается частота вертикальной передачи инфекции [15,16]. Участие урогенитальных микоплазм в развитии большого числа патологических состояний в гинекологии и акушерстве диктует необходимость своевременной диагностики и, при необходимости, этиопатогенетической терапии [5].…”
unclassified